Physical Therapists as Partners for Community Fall Risk Screenings and Referrals to Community Programs - Vincenzo, Jennifer L.; Hergott, Colleen; Schrodt, Lori; Perera, Subashan; Tripken, Jennifer; Shubert, Tiffany E.; Brach, Jennifer S. (Frontiers in Public Health, 2021)
Objectives: Research demonstrates that physical therapists conduct community-based fall risk screenings, resulting in uptake of fall prevention by older adults. We aimed to describe the characteristics of PTs who conduct screenings, knowledge and utilization of the STEADI, referrals to evidence-based programs (EBPs) and community resources, and the reach of screenings. Methods: A cross-sectional survey distributed to a convenience sample of PTs through news-blasts, and social media. Results: Approximately 40% of the respondents (n= 444) conduct screenings, most frequently annually. PTs who screen tend to have >20 years of experience, work in outpatient/wellness or academia, and have the least patient care. Over 80% use the STEADI and 75% are aware of and refer older adults to EBPs. Over half also refer to Silver Sneakers and/or senior centers. Discussion: Many physical therapists conduct community-based falls screening annually and refer older adults to community resources. Physical therapists can serve as community partners to promote community-based fall prevention and referral to EBPs and community resources.